Fault Growth and Interactions in a Multiphase Rift Fault Network: Horda Platform, Norwegian North Sea - Duffy,OB; Bell,RE; Jackson,CA-L; Gawthorpe,RL; Whipp,PS (Journal of Structural Geology, 2015)
Physical models predict that multiphase rifts that experience a change in extension direction between stretching phases will typically develop non-colinear normal fault sets. Furthermore, multiphase rifts will display a greater frequency and range of styles of fault interactions than single-phase rifts. Although these physical models have yielded useful information on the evolution of fault networks in map view, the true 3D geometry of the faults and associated interactions are poorly understood. Here, we use an integrated 3D seismic reflection and borehole dataset to examine a range of fault interactions that occur in a natural multiphase fault network in the northern Horda Platform, northern North Sea. In particular we aim to: i) determine the range of styles of fault interaction that occur between non-colinear faults; ii) examine the typical geometries and throw patterns associated with each of these different styles; and iii) highlight the differences between single-phase and multiphase rift fault networks. Our study focuses on a ca. 350 km2 region around the >60 km long, N-S-striking Tusse Fault, a normal fault system that was active in the Permian-Triassic and again in the Late Jurassic-to-Early Cretaceous. The Tusse Fault is one of a series of large (>1500 m throw) N-S-striking faults forming part of the northern Horda Platform fault network, which includes numerous smaller (2-10 km long), lower throw (<100 m), predominantly NW-SE-striking faults that were only active during the Late Jurassic to Early Cretaceous. We examine how the 2nd-stage NW-SE-striking faults grew, interacted and linked with the N-S-striking Tusse Fault, documenting a range of interaction styles including mechanical and kinematic isolation, abutment, retardation and reactivated relays. Our results demonstrate that: i) isolated, non-interacting and abutting interactions are the most common fault interaction styles in the northern Horda Platform; ii) pre-existing faults can act as